Peruvian foreign policy and the African continent: designing a strategy for closer engagement - Lembcke Hoyle, Gustavo (2024)
Since the 1990s, a number of African countries have begun a process of modernization of their economies, liberalizing their foreign trade, improving their infrastructure and taking steps towards digitalization, which has stimulated the sustained growth of their economies. The guidelines of the Reinforced Peruvian Foreign Policy aim to take advantage of the new African horizon, expanding Peru’s presence in that continent. The present article rehearses a strategy to achieve the formation of a partnership for development together with African nations.